2014
DOI: 10.1186/1546-0096-12-37
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki disease in children and adolescents: clinical data of Kawasaki patients in a western region (Tyrol) of Austria from 2003–2012

Abstract: BackgroundKawasaki disease (KD) is a rare vasculitis seen predominantly in children. In developing countries, it is the leading cause of childhood-acquired heart disease. Besides a case report from 1981 there have been no data published dealing with the epidemiology and clinical aspects of KD in Austria.MethodsThe purpose of the present study was to investigate the clinical spectrum of KD in a geographically determined cohort of infants, children, and adolescents that were diagnosed and treated at the Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
2
8
2
Order By: Relevance
“…Other studies reported the disease more frequently occured in boys [16,17]. However, our result has a discrepancy with those results, but is consistent with the data recently reported from Australia [18]. On this issue, a study including a larger number of patients will lead to more convincing conclusion.…”
Section: Discussionsupporting
confidence: 81%
“…Other studies reported the disease more frequently occured in boys [16,17]. However, our result has a discrepancy with those results, but is consistent with the data recently reported from Australia [18]. On this issue, a study including a larger number of patients will lead to more convincing conclusion.…”
Section: Discussionsupporting
confidence: 81%
“…In the presented study, 60 cases of KD patients were involved in this retrospective analysis and divided into 5 groups according to the children's different age interval. There are no obvious differences in the sex distribution as to the incidence of KD in all groups, which has a discrepancy with other studies showing the disease more frequently occurs in boys [13,14] but is consistent with the data recently reported in Australia [15]. A larger number of patients enrolled will have more convictive conclusion in this issue.…”
Section: Discussionsupporting
confidence: 77%
“…There are no obvious differences in the sex distribution in terms of the incidence of KD in all groups. This result shows a discrepancy with other studies, which show the disease more frequently occurs in boys [14,15] but is consistent with the data recently reported in Australia [16]. On this issue, including a larger number of patients will lead to more convincing conclusion.…”
Section: Discussioncontrasting
confidence: 61%